Pemanfaatan Media Sosial Facebook Sebagai Media Pemenuh Kebutuhan Informasi Bagi Penyandang Tunanetra - Azizaha, Nur; Edlina, Ria (CV. ITTC INDONESIA, 2024)
This study aims to find out how the use of social media, especially Facebook, as a means of fulfilling information needs for people with visual disabilities at the Bina Netra Tuah Sakato Social Home and what are the obstacles in its use. Technological developments, including social media, have provided wide access to users from all walks of life to communicate, share content, and get information. For people with visual impairments, the accessibility of social media such as Facebook can be important in filling their free time, sharing activities, and finding information relevant to their interests. The method used in this study is a qualitative research method. The results showed that the informants have various different motivations in using Facebook based on the purpose of each informant. The use of Facebook provides satisfaction for each informant. And from the interview results the results obtained that Facebook provides satisfaction in accordance with the purpose of using each informant. And obstacles in the utilization of Facebook by blind people cannot be separated from the limitations they have.